A estabilização da tutela de urgência antecipatória concedida em caráter antecedente - Bacha, Ahmad Jamal Ahmad El (2019)
The object of study of this dissertation is the stabilization of the previously granted antecipatory urgency order. This is a novelty in the brazilian procedural system brought by the Civil Procedure Code of 2015. The central idea of stabilization is that the respective decision produces and maintains its effects, regardless of the continuity of the process of full cognition, when the parts comply with it. It aims at improving the mechanisms for providing judicial protection, especially in the light of the constitutional principles of inability of the jurisdiction and the reasonable duration of the process, as well as of the reduction of the costs of the process, attending not only a private interests of the parts, but also a public interest. The objective of this work is, based on legislation, relevant doctrine and jurisprudence, to address several issues posed by the stabilization phenomenon, a task performed in its chapter IV. Its first three chapters deal respectively with the historical evolution of provisional protection, the discipline assigned to it by the italian, french, portuguese, german and common law legal systems, and other aspects concerned to the institute, such as procedures of the anticipatory and precautionary urgency orders previously required and the evidence protection